A Corpus of Syriac incantation bowls : Syriac magical texts from Late-Antique Mesopotamia - Moriggi, Marco. (Magical and Religious Literature of Late Antiquity, 2014)
The Aramaic incantation bowls from Sasanian Mesopotamia are the most important source we have for studying the everyday beliefs of the Jewish, Christian, Mandaean, Manichaean, Zoroastrian and Pagan communities on the eve of the Islamic conquests. In A Corpus of Syriac Incantation Bowls , Marco Moriggi presents new editions of forty-nine Syriac incantation bowls that were originally published between 1853 and 2012, with accompanying introductions, translations, philological notes, photographs and glossaries. Furthermore, there is a detailed analysis of the Estrangela and Manichaean scripts as used on the bowls, together with newly drawn script charts. In gathering, organising and updating most of the published Syriac bowls, this book provides a valuable resource for further research into both their language and content. \'This volume is a significant contribution to the study of the Syriac incantation bowls, and it should be of great interest to scholars of 'magic' in Late Antiquity as well as to those working in Syriac language, literature, and history, since the Syriac incantation bowls are a fascinating-yet often neglected-component of the broader Syriac heritage.\' - Aaron M. Butts , The Catholic University of America - Washington D.C., JNES (October 2015) . \'Moriggi's new book will no doubt become an essential reference work for all interested in Syriac magical texts from late-antiquity. It is also an important contribution not only to our knowledge of the language of the Syriac incantation bowls, but to the whole field of Babylonian Aramaic (JBA and Mandaic).\' - Ohad Abudraham , Ben-Gurion University of the Negev - Beer Sheva, Israel, Orientalia (2015) . \'The volume certainly makes an enormous contribution to furthering studies on Syriac incantation texts, and more generally on incantation bowls. For any scholar who has an interest in incantation bowls, this work is a 'mustʼ\' - Erica C. D. Hunter , SOAS University of London, Orientalistische Literaturzeitung 113.1 (2018) .